The Influence of Brand Image and Promotion on Consumer Purchase Decisions of Somethinc Products through the TikTok Shop Application - Mia Maulidia Putri; Fenni Supriadi (Electronic Journal of Education, Social Economics and Technology, 2025)
This study investigates the influence of brand image and promotion on consumer purchasing decisions for Somethinc skincare products through the TikTok Shop platform. Using a quantitative associative approach, data were collected through questionnaires from 100 respondents who met specific criteria. The analysis employed multiple linear regression, partial (t-test), and simultaneous (F-test) hypothesis testing, supported by classical assumption tests. The findings reveal that both brand image and promotion significantly influence purchasing decisions, with a regression model of Y = 1.413 + 0.370X₁ + 0.314X₂. The coefficient of determination (R²) value of 0.453 indicates that 45.3% of the purchasing decision variation is explained by the independent variables, while the remaining 54.7% is influenced by other factors. The t-test results show that brand image and promotion each have a positive and significant impact. These results suggest that a strong brand identity, supported by effective and adaptive promotional strategies via TikTok, is crucial in shaping consumer behavior. The study recommends that brands maintain a consistent image and continue leveraging social media platforms to engage young digital consumers. Future research is encouraged to include additional variables and explore other e-commerce platforms.